Neuroprotective effects of minocycline on focal cerebral ischemia injury: a systematic review - Yazdan Naderi (Neural Regeneration Research, 2020)
To review the neuroprotective effects of minocycline in focal cerebral ischemia in animal models. By searching in the databases of PubMed, ScienceDirect, and Scopus, and considering the inclusion and exclusion criteria of the study. Studies were included if focal cerebral ischemia model was performed in mammals and including a control group that has been compared with a minocycline group. Written in languages other than English; duplicate data; in vitro studies and combination of minocycline with other neuroprotective agents were excluded. Neurological function of patients was assessed by National Institute of Health Stroke Scale, modified Rankin Scale, and modified Barthel Index. Neuroprotective effects were assessed by detecting the expression of inflammatory cytokines. We examined 35 papers concerning the protective effects of minocycline in focal cerebral ischemia in animal models and 6 clinical trials which had evaluated the neuroprotective effects of minocycline in ischemic stroke. These studies revealed that minocycline increases the viability of neurons and decreases the infarct volume following cerebral ischemia. The mechanisms that were reported in these studies included anti-inflammatory, antioxidant, as well as anti-apoptotic effects. Minocycline also increases the neuronal regeneration following cerebral ischemia. Minocycline has considerable neuroprotective effects against cerebral ischemia-induced neuronal damages. However, larger clinical trials may be required before using minocycline as a neuroprotective drug in ischemic stroke.